Assessing the Level of Cybersecurity Awareness and Practices of Application Users and Their Impact on Privacy Policy Consents: A Case Study in Application Downloading - Sabah Abdellatif Hassan Ahmed (International Journal of Computers and Informatics, 2024)
The aim of this study is to understand the level of cybersecurity awareness and practices of application users and determine the impact on their consent to privacy policies through a case study in application downloading. To achieve this aim, this study employs quantitative research methodology. The primary data collection instrument is a structured questionnaire designed to gather insights and perspectives from 65 participants of application users in the Kingdom of Saudi Arabia, including several types of applications. The collected data was collected and analyzed using SPSS software. The findings revealed that most of the study participants disagree that they understand the importance of cybersecurity measures when using mobile applications with a frequency of 27 and a percentage of 41.5%. Also, most of the study participants disagree that they are aware about negative cybersecurity practices with a frequency of 26 and a percentage of 40%. Furthermore, only 23 participants are paying attention to Download applications from only official app stores or trusted sources with a percentage of 35.4% The findings of the study also revealed that a p-value related to Pearson Chi-Square is (0.019) which is less than a significance level of (0.05), this proves a significant statistical relationship between cybersecurity awareness and practices of application users on privacy policy consents.